A Simple Awareness For Women About (SAWA) stages of labor on women's childbirth experience using the childbirth roadmap tool: a quasi-experimental study - Fouly, Howieda; Gaber Zaghloul, Mervat; Alshiekh, Intisar; Masoud, Ayat (Jurnal Ners, 2023)
Introduction: Women's knowledge regarding childbirth progress can increase their comfort and satisfaction during labor. This study aimed to assess the effectiveness of the Simple Awareness for Women About (SAWA) labor stages program on their childbirth experience using the childbirth roadmap tool. Methods: A pretest and posttest technique was employed and conducted at the Labor Department, Woman Health Hospital, affiliated to the Assiut University Hospitals, Egypt. Based on the eligibility criteria, a convenient sampling method was used to recruit all parturient women admitted between June 2017 and August 2017. The sample consisted of 172 participants.  Results: A statistically significant difference was observed in the baseline information regarding the stages of childbirth subsequent to the SAWA program implementation. There was a significant relationship between the mode of delivery and the participant's satisfaction with the study tool. Conclusion: This study highlighted the benefits of using a simple, attractively illustrated instrument, the childbirth roadmap, for achieving the meaning of support through the SAWA program during labor stages.